Vpu and BST2: Still Not There Yet? - Sato, Kei; Gee, Peter; Koyanagi, Yoshio (Frontiers in Microbiology, 2012)
Extensive investigations have identified two cellular proteins in humans that potently inhibit HIV-1 replication and are widely accepted as ‘restriction factors’. APOBEC3G was identified as the restriction factor that diminishes HIV-1 replication by inducing G-to-A hypermutation in the viral genome, while BST2 has been identified as another restriction factor that impairs the release of nascent virions by tethering them on the surface of infected cells. To counter these restriction factors, HIV-1 has equipped itself with its own weapons: Vif degrades APOBEC3G, while Vpu antagonizes BST2. These findings have allowed us to further our understanding of virus-host interaction, namely, the interplay between viral factors versus host restriction factors. In the first case, the interplay between APOBEC3G and Vif is clear: vif-deficient HIV-1 is incapable of replicating in APOBEC3G-expressing cells. This insight directly indicates that APOBEC3G is a bona fide restriction factor and has intrinsic immunity against HIV-1, and that Vif is a prerequisite for HIV-1 infection. In other words, the relationship between Vif and APOBEC3G has already ‘matured’, and Vif has highly evolved to overcome APOBEC3G. On the other hand, although BST2 drastically impairs the release of vpu-deficient HIV-1 virions, it is puzzling that vpu-deficient HIV-1 is still able to replicate in BST2-expressing cells. These insights imply that BST2-mediated anti-HIV-1 activity is vulnerable, and that Vpu is dispensable for HIV-1 infection. If so, why has Vpu acquired the counteracting potential against BST2? Was it necessary or important for HIV-1? Or is the relationship between Vpu and BST2 still ‘immature’? In this review, we particularly focus on the interplay between Vpu and BST2. We discuss the possibility that Vpu has evolved as a potent antagonist against BST2, and finally, propose a hypothesis that Vpu has evolved as a promoter of human-to-human HIV-1 transmission. Since the first report of AIDS pati